RETRACTED: Bacteriological investigation of pyelonephritis in AL-Najaf Governorate, Iraq: a cross-Sectional study - Al-janabi Dhafer Rahman Abed; Aljanaby Ahmed Abduljabbar Jaloob (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001